Clinical course and prevalence of obesity associated with sphincter of Oddi dysfunction by pancreatic type in adolescents - I.S. Lembryk; O.O. Tsitsyura; R.Yu. Pryimak (Zaslavsky O.Yu., 2019)
Background. Gastroenterological manifestations of obesity is a topical problem of medicine in terms of mutually burdened nature. The purpose was to study the prevalence and clinical features of disease in adolescents with alimentary-constitutional obesity and concomitant sphincter of Oddi dysfunction by pancreatic type, or without such combination. Materials and methods. One hundred twenty adolescents with alimentary-constitutional obesity alone or in combination with sphincter of Oddi dysfunction by pancreatic type were examined. They were treated according to modern protocols of diagnosis and treatment in the Ivano-Frankivsk Regional Children's Clinical Hospital for the period from 2016 through 2019. Results. The prevalence of obesity in Ukraine, according to statistics, was 13.4 % per 1,000 children, which confirms the optimization of the diagnosis of this pathological condition compared to European data (10-15 % per 1,000 children population). We have found that among the examined children, males prevailed (70.0 and 30.0 %, p < 0.05). In majority of children with combined pathology, the duration of illness before admission to the hospital was 6.0 ± 2.1 years, with isolated course of the disease - 4.5 ± 3.1 years. The main risk factors for the pancreatic involvement are: genetic predisposition, low physical activity and diet violations, less frequently - insufficient fluid intake. Among the clinical manifestations of combined pathology, spastic pain with localization in the left subcostal region, which persisted for several hours and was poorly controlled by pain killers (75.0 and 25.0 %, c2 = 17.69, p < 0.05), prevailed. The total dyspeptic index (abdominal distension and diarrhea) in children with combined pathology was higher than in the others (5.01 ± 0.06 points and 3.02 ± 0.04 points, p < 0.05). The intoxication index due to general weakness was higher in the cohort of children with alimentary-constitutional obesity and functional pancreatic disorder (7.02 ± 0.06 points and 3.50 ± 0.02 points, p < 0.05). Conclusions. Obesity is often combined with functional pancreatic pathology, and individual clinical and laboratory markers and risk factors for pancreatic involvement in the pathological process should be based on updated diagnostic and treatment protocols.